Sewage Sludge Microbial Structures and Relations to Their Sources, Treatments, and Chemical Attributes - Nascimento, Altina Lacerda; Souza, Adijailton Jose; Andrade, Pedro Avelino Maia; Andreote, Fernando Dini; Coscione, Aline Renée; Oliveira, Fernando Carvalho; Regitano, Jussara Borges (Frontiers in Microbiology, 2018)
Sewage sludges generation and their disposal have become one of the greatest challenges of the 21st century. They have great microbial diversity that may impact wastewater treatment plant (WWTP) efficiency and soil quality whether used as fertilizers. Therefore, this research aimed to characterize microbial community diversity and structure of 19 sewage sludges from São Paulo, Brazil, as well as to draw their relations to sludge sources [domestic and mixed (domestic+industrial)], biological treatments (redox conditions and liming), and chemical attributes, using molecular biology as a tool. All sludges revealed high bacterial diversity, but their sources and redox operating conditions as well as liming did not consistently affect bacterial community structures. Proteobacteria was the dominant phylum followed by Bacteroidetes and Firmicutes; whereas Clostridium was the dominant genus followed by Treponema, Propionibacterium, Syntrophus, and Desulfobulbus. The sludge samples could be clustered into six groups (C1 to C6) according their microbial structure similarities. Very high pH (≥11.9) was the main sludge attribute segregating C6, that presented very distinct microbial structure from the others. Its most dominant genera were Propionibacterium > > Comamonas > Brevundimonas > Methylobacterium ∼Stenotrophomonas ∼Cloacibacterium. The other clusters’ dominant genera were Clostridium > > Treponema > Desulfobulbus ∼Syntrophus. Moreover, high Fe and S were important modulators of microbial structure in certain sludges undertaking anaerobic treatment and having relatively low N-Kj, B, and P contents (C5). However, high N-Kj, B, P, and low Fe and Al contents were typical of domestic, unlimed, and aerobically treated sludges (C1). In general, heavy metals had little impact on microbial community structure of the sludges. However, our sludges shared a common core of 77 bacteria, mostly Clostridium, Treponema, Syntrophus, and Comamonas. They should dictate microbial functioning within WWTPs, except by SS12 and SS13.